Perdas visíveis na colheita mecanizada de cana-de-açúcar - Belphman, Patricia Veiga (2016)
This work was carried out with the objective of quantifying the visible losses of sugarcane in the mechanized harvest at different displacement speeds. The experiment was conducted in a cane area without burning, with spacing between rows of planting of 1.5 m with yields varying from 41.4 t ha-1 to 78.5 t ha-1 in the same experimental area, working with speeds of 3,4,5 and 6 km h-1, using the harvester John Deere 3520. Each treatment consisted of six rows taken sequentially alternating the operating speeds, and between these speeds hears a displacement of 15 meters for speed stabilization, between these rows was allocated the template with dimensions of 3m x 5m, totaling 15 m2 and collected All material left after harvest. The data were submitted to ANOVA, Tukey test at 5%, aiming to compare the variation of the losses related to the velocities and also analyzed by the descriptive statistics. Mediante uma variação das perdas em diferentes velocidades de deslocamento da máquina, não há diferença significativa. O índice de eficácia da manipulação (EM) ficou dentro do valor aceitável e o índice da matéria prima industrial (Pc), ficou entre 2,0% e 5,5%.